Impact of malolactic fermentation on low molecular weight phenolic compounds - Cabrita, Maria João (2009)
A reversed phase liquid chromatography-DAD method is proposed for analysis of major non-flavonoid phenolic compounds in wines. The method employed a mixture of acetic acid, water and methanol as eluents and was used to evaluate the impact of malolactic fermentation in low molecular phenolic compounds. The wines analyzed underwent different treatments, like the addition of a pectolytic enzyme or lysozyme, and the way malolactic fermentation was carried out—spontaneously or with the inoculation of two different commercial lactic bacteria. The main result observed was the disappearance of hydroxycinnamoyltartaric acids and the increase of resultant free forms, regardless the way malolactic fermentation was carried out.